Fieber’s unpublished colour plates allow reassessing some of his Cixius species (Insecta: Hemiptera, Fulgoromorpha, Cixiidae) - Kunz, Gernot; Holzinger, Werner E; Soulier-Perkins, Adeline (Zootaxa, 2018)
Franz Xaver Fieber was a leading Hemiptera taxonomist in the 19th century. The recent discovery of his unpublished drawings that go along with the original handwritten manuscript allow a reassessment of species descriptions from this century. In addition, we present an alphabet of Fieber’s handwriting. We give an overview on the Cixiidae species he had described and reassess the status of the species names Cixius brachycranus Scott, 1870, Cixius intermedius Scott, 1870, Cixius pinicola Fieber, 1876, Tachycixius venustulus (Germar, 1830) and Tachycixius distinctus (Signoret, 1865). T. venustulus and T. distinctus are regarded as valid species. The synonymy of C. pinicola with T. venustulus is invalidated and C. pinicola is placed in synonymy with T. distinctus.